Association Between Socio-Demographic Variables and Body Mass Index (BMI) among School-Going Adolescents: A Cross-Sectional Study in Pokhara (Interdisciplinary Research in Education, 2025)
The nutritional status of school adolescents is a determining factor that influences their present and future health, cognitive development, and academic success. This paper investigates the relationship between socio-demographic characteristics and nutritional status, as measured by body mass index (BMI), among school-going adolescents in Pokhara, Gandaki Province, Nepal. Using a cross-sectional survey research design, data were collected from 384 students aged 10 to 19 years. The sample included an equal number of male and female adolescents, with 54% from community schools and 46% from institutional schools. The study employed a structured self-administered questionnaire with closed-ended questions and anthropometric measurements, including height and weight. Descriptive statistics (i.e., central tendency and standard deviation) and bi-variate analysis (i.e., chi-square test) were utilized. The findings reveal that students’ age, grade, and fathers’ occupation were significantly associated with nutritional status (BMI) at p < 0.05 among adolescents. Results indicate that younger adolescents from community schools, aged 10-14 years, and those whose fathers were employed, are more likely to experience malnutrition, including both undernutrition and overnutrition. The study emphasizes the close relationship between socio-demographic variables (such as age group, grade, and parents’ occupation) and the nutritional status of school-going adolescents. It recommends school-based health promotion programs integrated with family environments to encourage healthy dietary behaviors and improve nutrition status.